In vitro antifungal susceptibility of clinical isolates of Fusarium from Colombia (2017)
ABSTRACT : Objective The aim of the present study was to evaluate the antifungal susceptibilities of isolates of Fusarium to amphotericin B, itraconazole and voriconazole. Methods The susceptibility of 44 isolates of Fusarium was tested by the E-test methodology. Results All the isolates were resistant to itraconazole, and 89 % and 54,5 % were resistant to amphotericin B and voriconazole, respectively. Discussion The results confirm the high level of resistance reported, regardless of the species or the strain of Fusarium involved. The high MICs level observed are worrying and suggest that new drugs are needed.